Factors Afeecting the High Rate of Turnover Among Part Time Life Insurance Agents at Malaysian Assurance Alliance (MAA) Seremban Branch - M. Barathi Dasar (1998)
This study explored factors that contribute to the high turnover of part time life insurance agents at Malaysian Assurance Alliance (MAA), Seremban Branch. A self administered questionnaire were used to collect data from 111 part time life insurance agents who left the business from the main list of 350 drop outs provided by MAA Seremban Branch. Simple random sampling was applied to select the respondents before ask them to answer the questionnaire. Perceptional questions were used to gauge factors that make them leave the profession. High commitment at the permanent work place, lack of salesmanship skills, conflict between dual career were found to be strong factors affecting the turnover. Other factors include high achievement quota from the agency force and high selling activities which were required in order to stay in this business. Bank Negara's ruling on commission percentages was also found affecting the turnover. This study recommend that more facilitating environment is needed to develop part time life insurance agents, especially from the agency and parent organisation. Therefore different treatment and privilege should be given to the MAA part time life insurance agents compared to full time life insurance agents. Since this study is highly perceptional, more empirical data is needed pertaining to the turnover rate among the full time and part time life insurance agents. By having more information, it will help to ensure that more rigorous and conclusive study to be done in future.